2022
DOI: 10.1101/2022.04.20.488939
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional atlas of the human immune response to 13 vaccines reveals a common predictor of vaccine-induced antibody responses

Abstract: Systems biology approaches have been used to define molecular signatures and mechanisms of immunity to vaccination. However, most such studies have been done with single vaccines, and comparative analysis of the response to different vaccines is lacking. We integrated temporal transcriptional data of over 3,000 samples, obtained from 820 healthy adults across 28 studies of 13 different vaccines and analyzed vaccination-induced signatures associated with the antibody response. Most vaccines induced similar kine… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…In contrast, the global classifier of vaccine responses identified herein performed as well as a classifier trained on any given vaccine and tested on that same vaccine. A similar finding is described in our companion paper by Hagan et al 31 that focuses on post-vaccination response to the same 13 vaccines and identified a global transcriptomic signature associated with antibody response when all the vaccines are synchronized before building a classifier.…”
Section: Discussionsupporting
confidence: 79%
“…In contrast, the global classifier of vaccine responses identified herein performed as well as a classifier trained on any given vaccine and tested on that same vaccine. A similar finding is described in our companion paper by Hagan et al 31 that focuses on post-vaccination response to the same 13 vaccines and identified a global transcriptomic signature associated with antibody response when all the vaccines are synchronized before building a classifier.…”
Section: Discussionsupporting
confidence: 79%
“…The early transcriptional events in B cells upon antigenic stimulation are of critical importance for the generation and maintenance of humoral immunity. Since other studies have reported associations between plasmablast transcriptional response (peaking at Day 7-8) and antibody titers following vaccination, our study sought to identify early (Day 8, plasmablast) transcriptional signatures in B cells that are highly correlated with vaccine-induced humoral immune outcomes ( 24 27 ). To achieve this, we fit linear models for each gene with the Day 8 gene expression as the covariate.…”
Section: Resultsmentioning
confidence: 99%
“…How to relate these findings to vaccine-induced protection from infection and disease is unknown and reveals current limitations in the field of vaccinology. Identification of pre-and post-immunization immune profiles or transcriptional responses from blood with the goal of identifying profiles that correlate with optimal vaccine performance is being actively studied [28,36]. A recent publication evaluated 13 different vaccines and showed that a pre-vaccination pro-inflammatory endotype that included upregulation of genes encoding for pathogenassociated molecular patterns correlated with a better response to vaccination [28].…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication evaluated 13 different vaccines and showed that a pre-vaccination pro-inflammatory endotype that included upregulation of genes encoding for pathogenassociated molecular patterns correlated with a better response to vaccination [28]. Post-vaccination gene expression from these same individuals identified vaccines that clustered into groups based on similar immune responses, even though there was a heterogenous response between these clusters [36]. Such studies show the possibility of systems vaccinology to identify pre-vaccination states and vaccination types or adjuvants that could perform better in individuals or populations depending on age, health status, or with previous or current pathogen exposure.…”
Section: Discussionmentioning
confidence: 99%